Fibrilación auricular como factor de riesgo de acontecimientos cerebrovasculares en personas mayores de 65 años: ¿es adecuada la práctica clínica en profilaxis anticoagulante? - Gayoso Diz, P. (Aten Primaria, 2005)
AIM: To describe the clinical practice in antithrombotic therapy to prevent stroke in older patients with atrial fibrillation (AF). DESIGN: Cross-sectional study. SETTING: Ourense's area with 95 840 inhabitants over 65 years. PARTICIPANTS: Patients over 65 with non rheumatic AF, chronic or paroxistic; 411 cases, 69.6% older than 75 year. MAIN MEASUREMENTS: Demographic characteristics, personal history, stroke risk, diagnostic characteristics of AF, antithrombotic treatment, and its adequacy. RESULTS: Only 33% high risk patients received oral anticoagulation (OCA) with warfarin at diagnosis. Some features were found to be significant independent risk factors for OCA: age (older than 75 vs 65-74 years; odds ratio =0.32; 95% confidence interval, 0.18-0.59), and prior stroke (odds ratio =2.02; 95% confidence interval, 1,16-3,55). CONCLUSIONS: Warfarin prophylactic is insufficiently prescribed, especially in older than 75 years (with high baseline risk of stroke and no counter-indications). There was inadequate prescription in 73.4% cases.